Cognition and Pain: A Review - Khera, Tanvi; Rangasamy, Valluvan (Frontiers in Psychology, 2021)
Cognition is defined as the brain’s ability to acquire, process, store, and retrieve information. Pain has been described as an unpleasant sensory or emotional experience, and for experiencing pain consciously, cognitive processing becomes imperative. Moreover, evaluation of pain strongly depends on cognition as it requires learning and recall of previous experiences. There could be a possible close link between neural systems involved in cognition and pain processing, and studies have reported an association between pain and cognitive impairment. In this narrative review, we explore the available evidence that has investigated cognitive changes associated with pain. We also examine the anatomical, biochemical, and molecular association of pain and neuro-cognition. Additionally, we focus on the cognitive impairment caused by analgesic medications. There is a need to improve our understanding of pathophysiology and cognitive impairment mechanisms associated with chronic pain and its treatment. This area provides a diverse opportunity for grounding future research, aiding institution of timely interventions to prevent chronic pain and associated cognitive decline, ultimately improving patient care.